HUBUNGAN ANTARA BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN LOCUS OF CONTROL TERHADAP KINERJA MANAJEMEN - Widodo, Purwanto; Kamilah, Ahya (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
This research intent to see relationship among cultural organisational, organisational commitment and Locus of Control at PTS in Jabar. Observational population is lecturer and employee staff at environmentally PTS of 188 person, employee and lecturer at PTS X most takings 87 respondents or 4,28 percents. That respondent comprise of 47 men and 53 woman percents. Job unit broadcast scatters, Fisip's majority, Economy and FAI. Largely respondent gets S1's education (36,78 percents), S2(28,74 percents) and diploma 14,94 percents. Picture gets that that more komprehensif, therefore data processing is done by use of Structural Equation Model (SEM). Validity quiz and reliabitas is first phase to item question, pointing out result that vaid and reliable, meanwhile on phase II., are not all item that question valid and reliable. Analisis's result points out that together to be gotten relationship among cultural organisational, organisational commitment and locus of control to manajerial dengn's performance R Square 0,32. Sign from variable the whole lot in accordance with expectation which is positive, but just variable locus of control just that don't signifikan statistic's ala.